Analisis Pengaruh Pembiayaan Murabahah, Musyarakah dan Mudharabah Terhadap Profitabilitas Bank Pembiayaan Rakyat Syariah di Indonesia Dengan Non Performing Financing (NPF) Sebagai Variabel Moderasi Periode 2017-2020 - Siti Faizah; Hesi Eka Puteri; Reina Tasha Baskara; Vewi Julita; Anwar Sholihin (ITB AAS INDONESIA Surakarta, 2023)
This research is motivated by the existence of phenomena that occur that are not in accordance with existing theories and the existence of inconsistent previous research. This study aims to determine the effect of Murabahah Financing, Musyarakah Financing and Mudharabah Financing on the Profitability of Islamic People's Financing Banks in Indonesia with Non-Performing Financing as a moderating variable for the 2017-2020 period. This study uses a quantitative approach. The data in this study used monthly time series data from 2017-2020 obtained from SPS OJK and analyzed using the PLS (Partial Least Square) analysis technique via Warp-PLS version 7.0. The results of the research on the first model (the effect of murabahah financing on bank profitability with NPF as a moderating variable) show that murabaha financing has a significant positive effect on bank profitability (ROA) by obtaining a sign p-value